2011
DOI: 10.1111/j.1528-1167.2011.03325.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life in pharmacoresistant epilepsy: Results from a large multicenter study of consecutively enrolled patients using validated quantitative assessments

Abstract: SUMMARYPurpose: To evaluate the relative contribution of demographic and epilepsy-related variables, depressive symptoms, and adverse effects (AEs) of antiepileptic drugs (AEDs) to health-related quality of life (HRQOL) in adults with pharmacoresistant epilepsy. Methods: Individuals with epilepsy whose seizures failed to respond to at least one AED were enrolled consecutively at 11 tertiary referral centers. HRQOL was assessed by the Quality of Life in Epilepsy Inventory-31 (QOLIE-31), AEs by the Adverse Event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
145
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(168 citation statements)
references
References 55 publications
17
145
0
6
Order By: Relevance
“…Depression represents one of the most common comorbidities of epilepsy and has profound negative impact on the quality of life of patients. [33][34][35] It has been hypothesized that in patients with seizures dysregulation of the hypothalamus-pituitary-adrenal axis may cause deficit in the raphe-hippocampal serotonergic transmission and predispose to depression. 36 Similar mechanisms involving the alteration of serotoninergic transmission may explain the apparent clinical link between epilepsy and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Depression represents one of the most common comorbidities of epilepsy and has profound negative impact on the quality of life of patients. [33][34][35] It has been hypothesized that in patients with seizures dysregulation of the hypothalamus-pituitary-adrenal axis may cause deficit in the raphe-hippocampal serotonergic transmission and predispose to depression. 36 Similar mechanisms involving the alteration of serotoninergic transmission may explain the apparent clinical link between epilepsy and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacoresistance leads to shortened life spans due to a higher incidence of sudden deaths, Each value represents mean ± SEM for 6 mice PHB represents Phenobarbitone; MES represents maximal electroshock @ p value for comparison with normal control group # p value for comparison with PHB+MES group * p < 0.05; $ p > 0.05 psychiatric issues and other antiepileptic drugs (AEDs) related toxicities. 19 Pharmacoresistance is complex with even controlled patients relapsing and developing resistant epilepsy. While previously resistant patients would experience remission (about 4% of adults per year), of which a sizable proportion goes on to eventually relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Although use of the latter endpoints is acceptable for regulatory purposes, it is clear that being a responder according to these criteria does not necessarily imply having a clinically significant benefit. Indeed, many studies have shown that quality of life (QOL) in people with epilepsy is primarily conditional on achieving complete seizure freedom without intolerable adverse effects and is little affected by a simple reduction in the frequency of seizures 66. This concept is well illustrated by the findings of an RCT of vigabatrin in patients with focal seizures 67.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%